Heart rhythm safety of the mononuclear cord blood stem cells transplantation in patients with refractory ischemic heart failure - O.Yu. Usenko; A.V. Yakushev; O.V. Lisun; M.V. Kostylev; V.F. Onishchenko (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the safety of mononuclear cord blood stem cells transplantation regarding influence upon heart rhythm in patients with refractory heart failure Materials and methods. The work is based on the analysis of Holter-ECG monitoring data in 20 patients with refractory heart failure and reduced myocardial contractility. With the purpose of improvement of systolic function patients underwent transplantation of mononuclear cord blood stem cells. Results. Analysis of the probable proarrhythmogenic influence of mononuclear cord blood stem cells was performed in terms of follow-up during up to 9 months. Results demonstrated that administration of the cell preparation «Cryopreserved human cord blood» is not associated with increased risk of life-threatening cardiac arrhythmias. Conclusions.Transplantation of mononuclear cord blood stem cells should not be considered as an additional arrhythmogenic risk factor in patients with refractory heart failure.